Deviation from target capital structure as a factor of acquisition decisions in European developed markets - Mugoša, Ana; Popović, Saša (Publishing House of Wroclaw University of Economics and Business, 2021)
The purpose of this paper is to examine the causal relation between deviations from target capital structure (leverage deficit) and acquisition choices in capital markets in Western Europe. The analysis is conducted using a sample of 921 large companies, which represents a strong and solid base for testing target capital structure and takeover interdependence, as the focus is on the period when half of the largest M&A deals in Western Europe occurred. This study found that leverage deficit is a crucial determinant of acquisition choices and market reaction on acquisition announcements, measured by CARs to bidders. Companies that are underleveraged relative to their target capital structure have a higher probability of undertaking acquisitions. On the other hand, the market reacts unfavourably to acquisition announcements of underleveraged acquirers – overleveraged companies undertake the most value-enhancing acquisitions, whilst underleveraged companies make poor acquisition choices. This paper enriches the literature by empirically extending the understanding of how managers make investment decisions in relation to capital structure, and how capital markets assess the impact of these investments
Argumenta Oeconomica, 2021, Nr 1 (46), s. 53-78